HEALTH AND FAMILY SUPPORT ISSUES OF WOMEN REFUGEES AND RELATED NURSING INTERVENTION: A LITERATURE REVIEW: DOI: https://doi.org/10.35654/ijnhs.v2i1.55 - Hastoro Dwinantoaji; Mami Nojima; Nlandu Roger Ngatu (Alta Dharma Publisher, 2019)
Aim: Migration has become one of global human security issues of the 21st century. Women refugees face a unique set of problems and their health is often compromised. The aim of this study was to describe health and family support issues encountered by women refugees in refugee setting and related nursing interventions. Methods: A literature review was performed using Academic Search Premier, CINAHL and Medline databases, and the following keywords were used separately and in combination to retrieve related abstracts and articles: `women refugees`, `health`, `nursing`. Only original articles from qualitative studies published in English and focusing on women’s health and family support in the refugee setting were selected for the review. Results: Three major themes related to women refugees’ health issues were identified: `Culture sensitivity`, `Seeking life balance` and `Gender-based violence`. In addition, nine major themes related to family support were found: `Family reunion (difficulty to emigrate)`, `Changes in family’s connections and roles`, `Unsatisfactory family life`, `Discrimination and contempt by community`, `Health problems in children`, `Mental health problems in family member`, `Adjustment and adaptation of life pattern in a new country`, `Family time and togetherness` and `Concern about forgetting one’s homeland`. On the other hand, we identified 11 major themes related to nursing interventions implemented for women refugees. Conclusion: Disaster nurses have important role to protect and promote human security among women refugees. Future studies should determine how disaster nurses can efficiently promote human security for women in refugee setting.